School-based adolescent health survey in Himachal Pradesh, India: study design and protocol - Mohanty, Saroj; Mehra, Devika; Das, Subha Sankar; Sethi, Gaurav; Garg, Rishi; Gupta, Anmol; Chauhan, Anjali; Mehra, Sunil (Frontiers in Public Health, 2024)
BackgroundThe World Health Organization defined adolescent age group as a life span between 10 and 19 years. Adolescence is a phase of transition from childhood to adulthood, it is a unique stage for human development and a very sensitive period for laying the foundation of good health. Investment in this life-stage yields triple dividend. To promote health and well-being of adolescents, Government of India has launched various programs. An institutionalized evaluation of documenting achievement would strengthen these government led programs.MethodsA cross-sectional survey will be conducted among adolescents enrolled in government schools in the age group of 13–17 years. Two research instruments for students, principals, and for data collectors a checklist will be developed. Standard measures will be followed for data quality assurance. Data from students and principals will be collected in self-administration mode. Bivariate and multiple logistic regression will be employed for data analysis.ResultsThe study protocol for the school-based adolescent health survey will be implemented in Himachal Pradesh, India. The survey results will be disseminate both at state and national level.ConclusionThe study findings will provide policymakers and program planners with scientific evidence on key thematic areas essential for adolescent development and health outcomes. These insights will help identify and prioritize specific focus areas within the school health program, guiding more effective implementation strategies to address the unique needs of adolescents.